Firm Fundamentals, Corporate Life Cycle and Stock Market Crash: - Miah, Muhammad Shahin (STIE Malangkucecwara, 2025)
The main purpose of this study is to investigate the impact of firm fundamentals on the propensity of stock market crash. More specifically, this study shows whether there is any association between the movements of share prices and firms’ accounting components along with other determinants using listed companies in Dhaka stock exchange (DSE). To examine the conjecture, the present study conducts an in-depth analysis based on a sample of DSE listed companies from 2005 to 2011. Results of the study show that the firm’s profitability is highly correlated with the stock price which indicates that shareholders emphasize, mostly, the firm’s profitability before making their investment decisions. However, we do not find any association between share price and other accounting components in this study, which is contradictory with the extant capital market research. Further, the present study presents the impact of firm life cycle stages on the association between accounting components and stock prices. Overall, this paper contributes to literature of capital market research by providing empirical evidence. Nevertheless, this paper contributes to the policy making regarding capital markets and it provides a set of recommendations to attenuate the possibility of future capital market crash in emerging economies.